Cabbage pest control with local inert dusts: do diatomaceous earth and wood ash have the highest potential? - Luka Batistič; Tanja Bohinc; Monica Novljan; Eva Indihar; Iztok Jože Košir; Urban Šilc; Aleksander Horvat; Stanislav Trdan (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Cabbage (Brassica oleracea var. alba) production in Europe faces challenges from insecticide resistance and environmental concerns. Inert dusts offer a promising alternative, but their field efficacy remains underexplored. Over two growing seasons, we conducted a three-block field investigation with seven treatments (zeolite, quartz sand, diatomaceous earth, wood ash, Ailanthus altissima dust, a positive control [Spinosad] and a negative control [untreated plants]) on a cabbage field. In the first, dry season, we found that diatomaceous earth and wood ash were most effective, reducing damage indices for Eurydema spp., flea beetles and lepidopteran larvae. A. altissima dust showed the best results against onion thrips. Diatomaceous earth also achieved the highest net and gross yield per cabbage head in the first growing season, significantly outperforming untreated control. The rainy, second growing season, reduced the efficacy of all inert dusts, with damage indices rising to 4 for all pest groups and net yields decreasing to ≈700 g per cabbage head. Although the positive control yielded higher, it still fell short of ideal levels. We found that diatomaceous earth and wood ash consistently outperformed other inert dust and the untreated control, with A. altissima dust being most effective against onion thrips.